Proyecto de factibilidad para la creación de una empresa de limpieza de residencias para la ciudad de Quito - Jaramillo Sarche, María Belén (2015)
The objective of this research is to determine the feasibility that will create a company dedicated to cleaning houses, located in the Metropolitan District of Quito, which allowed the application of different methods and techniques that allows research, as The inductive method it gave a guideline to determine the general conclusions of the project, the deductive method based on this sample size, with general and actual data of the population at the local level potential demand, real, effective it determined and unmet demand, the synthetic analytical method that allowed, applying management science and through which the generalizing laws of the company were determined, the statistical method instead possible to measure the results of the surveys, and the highest percentage was determined which allowed the problem to determine the feasibility of creating a residential cleaning company. In the market study in the city of Quito, with a sample of 400 families and 65 companies offering home cleaning services; Weighted surveys have been analyzed and the results have been inferred then undertake market analysis, determining the potential demand for 450,332 families, 81,060 actual demand, is the Effective Demand services 427 996 determined by the results of the analysis demand, supply and marketing levels for this product. The unmet demand reflects the potential that exists in the city aforesaid for the company, market with the following results: For the base year project life is unmet demand: 401.732 services, the installed capacity of the project determines the company It will be able percentage that has to provide the services, of which 100% of the unmet demand is determined. Then the project engineering process diagrams determining the characteristics of operation and management, technical requirements such as equipment, facilities, furniture and fixtures develops. Also an administrative study determined as a Limited Liability Company, and the functional organizational structure both hierarchical levels Legislative, Executive, Consultant Level Support Assistant, Operational Level Level as well as operating manuals, charts held; which they served as a guideline to implement good organization, since it will have the following staff: Manager, a secretary, a janitor-guardian, an accountant, a supervisor, who will be part of the administrative staff and operational staff. The project reaches an investment of $ 67,331.19 and will be financed by a contribution of the partners the 55,44% of the total investment corresponds to $ 37,331.19 and a loan that will keep the project with the National Finance Corporation 44,56% corresponding to $ 30,000 10-year term at 15.00% annual interest. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 48.836,29, which indicates that the project or investment is suitable. For this project, the IRR is 31.15%, this being satisfactory value for the project, the time required to recover the original investment would be 3 years, 11 months and 15 days, for this project, the sensitivity values They are less than one, thus not affecting the project changes in costs and increased revenue decreased 28.55% and 19.68%, respectively, ie the project is not sensitive to these changes